Biochemical purification of oil wastewater - Semenova, Olena; Smirnova, Elizabeth; Shylofost, Tatiana; Bublienko, Natalia (My University, 2012)
The given article discusses the problem of treatment of oil wastewater. It is known that the problem of oil wastewater treatment is topical nowadays, because as a result of various technical and technological processes the formed oil wastewater is not utilized properly. The article provides the information of pollution of oil wastewater which is produced by the food enterprise, and also the ways of its purification. The objective of research is the intensification of the process of biochemical treatment. Scientific novelty of the research lies in biosorbtion of oil gas-liquid countercurrent mode and oxidation in an airtank-clarifier.
Keywords: oil wastewater; pinotank; airtank; biochemical purification; стічні води; аеротенк; пінотенк; біохімічне очищення; нафтопродукти; кафедра екології та екоменеджменту; кафедра іноземних мов професійного спрямування